Ladybug Girl and the Dress-up Dilemma - Soman, David; Davis, Jacky 1966- (New York, New York : Dial Books for Young Readers, an imprint of Penguin Group (USA) Inc., 2014)
"It is Halloween and Lulu doesn't know if she should dress as Ladybug Girl or find a different costume for the special day"--
Keywords: Halloween -- Fiction; Costume -- Fiction; Halloween -- Juvenile fiction; Costume -- Juvenile fiction